Research Participation for Bereaved Family Members. Issue 9 (September 2015) - Kentish-Barnes, Nancy; McAdam, Jennifer L.; Kouki, Sonia; Cohen-Solal, Zoé; Chaize, Marine; Galon, Marion; Souppart, Virginie; Puntillo, Kathleen A.; Azoulay, Elie
<x xml:space="preserve">Abstract</x> Background: Research has highlighted potential negative health outcomes for bereaved family members after loss of a loved one in the ICU and has helped identify areas for intervention. The findings exist because these family members agreed to participate in research studies; but little is known about their experience of research participation. Objective: To understand why family members participate in bereavement research and the benefits of participating in such research. Design: Qualitative study using interviews with bereaved family members as well as letters written by bereaved family members. Setting: Forty-one ICUs in France. Subjects: Family members who lost a loved one in the ICU. Measurements and Main Results: Thematic analysis was used and was based on 54 narratives, 52 letters, and written annotations on 150 questionnaires. Regarding reasons to participate and benefits of research participation, 6 themes emerged: 1) to say thank you to the ICU team, 2) to help other bereaved family members, 3) to express myself from a distance, 4) to not feel abandoned, 5) to share difficult emotions and to help make meaning of the death, and 6) to receive support and care. Conclusion: Bereavement research is possible after loss of a loved one in the ICU and may even be beneficial for family members. Exploring families' experiences of research participation helps define specific family needs in this setting. After the loss of a loved one in the ICU, bereaved families need opportunities to voice their feelings about their experience in the ICU and to give meaning to the end-of-life process; families also need to feel that they are still cared for. Support for the family may need to be developed after loss of a loved one in the ICU in the form of condolence letters, phone calls, or postintensive care meetings.